'Eternal Recurrence': development of a 3D water curtain system and real-time projection mapping for a large-scale systems artwork installation. Issue 2 (2nd April 2020) - Sohn, Youngsil; Park, Yoenyong; Lin, Longchun; Jung, Moonyurl
ABSTRACT: 'Eternal Recurrence' is a large-scale installation work consisting of a 3D water curtain and projection mapping systems. A 3D water curtain, water drop generation and control program, fog screen and computer program for recognizing visitors were developed for this work. The water curtain, implemented using an array of solenoid valves, creates ephemeral sculptures in real time; the continuous evolution of shapes and images is used as a metaphor of Eternal Recurrence. We developed a method of controlling the solenoid valves that avoids problematic vertical shape distortion caused by gravity and noisy satellite water droplets around the main water drops. The motion of the falling water drops at the centre of the installation is mirrored by the motion of baby-like shapes projected on to the floor and ceiling of the space in which this work is installed. This gives the impression of a full or completed circle. Visitors enter the exhibition through a fog screen, which acts as an entrance port to this immersive experience. 'Eternal Recurrence' is a convergence of digital images (3D shape projections) with natural phenomena (falling water drops), which are carefully blended and controlled. As an example of systems art, the installation embodies a process in which all of the separate elements are seamlessly blended through a mechanical–electrical–computer system. The creation and experience of this harmonious system help us to reconsider our existence and networked relations in contemporary society.